Correspondences between retinotopic areas and myelin maps in human visual cortex - Abdollahi, Rouhollah O.; Kolster, Hauke; Glasser, Matthew F.; Robinson, Emma C.; Coalson, Timothy S.; Dierker, Donna; Jenkinson, Mark; Van Essen, David C.; Orban, Guy A. (NeuroImage (Orlando, Fla.), 2014)
We generated probabilistic area maps and maximum probability maps (MPMs) for a set of 18 retinotopic areas previously mapped in individual subjects (Georgieva et al., 2009 and Kolster et al., 2010) using four different inter-subject registration methods. The best results were obtained using a recently developed multimodal surface matching method. The best set of MPMs had relatively smooth borders between visual areas and group average area sizes that matched the typical size in individual subjects. Comparisons between retinotopic areas and maps of estimated cortical myelin content revealed the following correspondences: (i) areas V1, V2, and V3 are heavily myelinated; (ii) the MT cluster is heavily myelinated, with a peak near the MT/pMSTv border; (iii) a dorsal myelin density peak corresponds to area V3D; (iv) the phPIT cluster is lightly myelinated; and (v) myelin density differs across the four areas of the V3A complex. Comparison of the retinotopic MPM with cytoarchitectonic areas, including those previously mapped to the fs_LR cortical surface atlas, revealed a correspondence between areas V1–3 and hOc1–3, respectively, but little correspondence beyond V3. These results indicate that architectonic and retinotopic areal boundaries are in agreement in some regions, and that retinotopy provides a finer-grained parcellation in other regions. The atlas datasets from this analysis are freely available as a resource for other studies that will benefit from retinotopic and myelin density map landmarks in human visual cortex. •Maximum probability maps for 18 retinotopic areas were generated.•Multimodal surface matching was used to compare with myelin and cytoarchitectonic maps.•Early areas V1–3 areas are heavily myelinated, as are V3D and most of areas MT/pMSTv.•The phPIT cluster is lightly myelinated compared to other retinotopic areas.•Early areas V1–3 correspond to areas hOc1–3, with little correspondence beyond V3.